2022
DOI: 10.1021/acsami.2c12772
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Electrochemical Nitrate Reduction to Ammonia on a Co3O4 Nanoarray Catalyst with Cobalt Vacancies

Abstract: Electrocatalytic nitrate reduction reaction (NO 3 RR) affords a bifunctional character in the carbon-free ammonia synthesis and remission of nitrate pollution in water. Here, we fabricated the Co 3 O 4 nanosheet array with cobalt vacancies on carbon cloth (v Co -Co 3 O 4 /CC) by in situ etching aluminum-doped Co 3 O 4 /CC, which exhibits an excellent Faradaic efficiency of 97.2% and a large NH 3 yield as high as 517.5 μmol h −1 cm −2 , better than the pristine Co 3 O 4 /CC. Theoretical calculative results impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 61 publications
0
50
0
Order By: Relevance
“…The BET specific surface area of the irregular Ce 0.8 Zr 0.2 O 2 support (CZ-irg) was 24.9 m 2 /g, lower than that of the Ce 0.8 Zr 0.2 O 2 nanorod support. It suggested that the nanorod support could provide a larger specific area, which is beneficial to Ni dispersion and catalytic activity . After loading with Ni, both the BET surface area and total pore volume decreased.…”
Section: Resultsmentioning
confidence: 99%
“…The BET specific surface area of the irregular Ce 0.8 Zr 0.2 O 2 support (CZ-irg) was 24.9 m 2 /g, lower than that of the Ce 0.8 Zr 0.2 O 2 nanorod support. It suggested that the nanorod support could provide a larger specific area, which is beneficial to Ni dispersion and catalytic activity . After loading with Ni, both the BET surface area and total pore volume decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, for instances, the CuO x /CuF catalyst with electrodeposition parameters of 400 s and −1.0 V attained a higher NH 4 + yield of ∼14 μmol h −1 cm −2 mM [NOd x ] at a lower potential of −0.5 V, as compared to FSP-CuO (∼6 μmol h −1 cm −2 mM [NOd x ] at −0.6 V), 15 Pd-TiO 2 (∼0. 42 Ru-ST-12 (∼1 μmol h −1 cm −2 mM [NOd x ] at −0.8 V), 43 Cu/Ni foam (∼5 μmol h −1 cm −2 mM [NOd x ] at −0.8 V), 20 and CF@Cu 2 O (∼7 μmol h −1 cm −2 mM [NOd x ] at −1.0 V). 22 mM [NOd x ] at −0.45 V) 18 and Cuboctahedron Pd/C (∼0.02 μmol h −1 cm −2 mM [NOd x ] at −0.2 V).…”
Section: T H Imentioning
confidence: 99%
“…Nevertheless, NO 3 RR activity is restricted by its complex eight-electron process and some side reactions including the HER, and thus efficient NO 3 RR catalysts are required to accelerate the NO 3 RR reaction kinetics while suppressing the side reactions. 17–30…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, NO 3 RR activity is restricted by its complex eight-electron process and some side reactions including the HER, and thus efficient NO 3 RR catalysts are required to accelerate the NO 3 RR reaction kinetics while suppressing the side reactions. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] MoS 2 has been extensively confirmed to be able to effectively electroreduce nitrogenous molecules into diverse value-added chemicals owing to the nitrogenase-analogous characteristic of Mo active sites, [31][32][33][34][35] as well as its other merits of a layered structure, natural abundance, ease of synthesis and high electrochemical stability. 36 Nevertheless, the investigations of MoS 2 -based electrocatalysts are quite limited for the NO 3 RR due possibly to their low electrical conductivity and poor intrinsic NO 3 RR activity.…”
Section: Introductionmentioning
confidence: 99%